تطور مؤشرات النقل في المؤسسة العامة للخطوط الحديدية السورية 1980-2004 وصياغة نموذج رياضي للتنبؤ المستقبلي بحجوم نقل البضائع - بدر, يعرب; الأعرج, مضر; اسكيف, ربيعة (Latakia University Journal -Engineering Sciences Series, 2019)
لقد برهنت خدمات النقل بوساطة الخطوط الحديدية عالمياً بأن هذا النمط يتمتع بالعديد من الخصائص, والمزايا تؤهله لأن يكون في المقام الأول لكونه صديقاً للبيئة, فضلاً عن متعة السفر ومرونة الحركة في أثناء الرحلات وعوامل الراحة والأمان, فضلا عن إمكانية نقل حجوم نقل كبيرة من البضائع والركاب بسرعة عالية. نقدم في هذا البحث عرضا تحليليا لتطور مؤشرات النقل في المؤسسة العامة للخطوط الحديدية السورية في الفترة 1980-2004 من خلال استعراض واقع الأدوات المحركة والمتحركة، وتبيان وضع الشبكة وبالتالي تحديد بعض أسباب انخفاض معدلات الأداء. كما يتضمن البحث دراسة إحصائية تحليلية تفصيلية لسلسلة حجوم البضائع خلال الفترة 1987-2005 باستخدام نموذج الجداء لمركبات السلسلة الزمنية المدروسة، حيث توصلنا إلى نموذج رياضي يمكننا من التنبؤ المستقبلي بحجوم البضائع المنقولة بالخطوط الحديدية السورية. وقد تم تقديم مجموعة من المقترحات والتوصيات التي تساعد على رفع كفاءة أداء هذه المؤسسة. The rail transportation has proved that it has many specifications and advantages which make it number one internationally, because it's environment-friendly, and provides traveling comfort, flexibility of movement, safety and comfort during journeys, let alone its ability to transport a large number of passengers and huge volumes of freight at high speed. We present in this paper an analytical study of the transportation references development in the General Establishment of Syrian Railways, during 1980-2004 by discussing the status of towed and towing equipment, and the condition of the network. Then, we define some reasons for low performance averages in the Establishment. The paper also deals with a statistical analytical study of freight volumes during 1987-2005 by using a multiplication model of the time series; so we find a mathematical model explaining the possibility prediction of future freight volumes. A set of proposals and recommendations have been put forward to help develop and raise the efficiency performance of the General Establishment of Syrian railways.